South Asian Atlantic Literature, 1970-2010 - Maxey, Ruth (Edinburgh Studies in Transatlantic Literatures, 2011)
The first major interpretation of recent South Asian diasporic writing in specifically transatlantic terms.The book is organised around four key themes: home and nation; travel and return; racial mixing; and food and eating. Ruth Maxey offers readings of canonical and less well-known South Asian American and British Asian writers and texts and of key cinematic works. She explores the formal and thematic tendencies of the works, relating them to gender politics, the marketplace, and issues of literary value and historical change. The book engages with established debates, while intervening in new ways in transatlantic studies, postcolonial literary studies and Asian American cultural studies.